REVIEW IN CLOUD BASED NEXT GENERATION TELECOMMUNICATION NETWORK (Jurnal Teknologi (Sciences & Engineering), 2016)
The development of cloud computing technologies is rapidly accelerating the integration of telecommunications services and the Internet, by adopting the cloud model the telecommunications industry can on demand ,organize and apply telecommunication resources as a services .The NGN (Next Generation Network), and IMS (intelligent multimedia subsystem) are essentially developed to provide multimedia services over an all-IP based network, however the full realization of both solutions is still is not reachable and it is still far from being widely deployed specially for the IMS, this is despite the development that has been undergoing for years .The main reasons behind that, is theÂ  increasing demands by consumers, fast evolving access technologies , complexity of implementations to meet these growing demands. Cloud computing as fast evolving IT paradigm can be considered as solution for scalability issue of NGN and IMS which may lead to the full realization of NGN and IMS .This Paper presents literature review on researches and trials on cloud based NGN and IMS.